155 Cost-Effectiveness Analysis of Deep Brain Stimulation Versus Treatment as Usual for Treatment-Resistant Obsessive-Compulsive Disorder. (April 2023) - Najera, Ricardo Andres; Shofty, Ben; Anand, Adrish; Gadot, Ron; Storch, Eric; Goodman, Wayne; Sheth, Sameer A.
Abstract : INTRODUCTION: Deep brain stimulation (DBS) is an effective neurosurgical option for patients with treatment-resistant obsessive-compulsive disorder (TROCD). Despite being more costly than neuroablative procedures of comparable efficacy, DBS has gained popularity for its reversibility. Though its cost-effectiveness has been investigated in movement disorders, few economic analyses of DBS for psychiatric disorders exist. METHODS: We developed decision analytic models to compare the cost-effectiveness of DBS to treatment as usual (TAU) for TROCD, varying device type (non-rechargeable or rechargeable) or time-horizon (three or five years). Effectiveness data were based on literature review. Published algorithms were used to convert Y-BOCS scores into utilities. Costs were approached from the healthcare sector perspective and drawn from Medicare reimbursement rates. Monte Carlo (MC) simulations and probabilistic sensitivity analyses were performed to estimate the incremental cost-effectiveness ratio (ICER) in USD ($) per quality-adjusted life-year (QALY). RESULTS: We included 238 and 265 TROCD patients across 28 studies who underwent DBS and had sufficient follow-up in our 3- and 5-year models, respectively. Non-rechargeable DBS was less cost-effective than TAU (3-year ICER = $153, 221/QALY; 5-year ICER = $194, 043/QALY). Rechargeable DBS was moderately more cost-effective at three years (ICER = $70, 646/QALY) and definitively more cost-effective at five years (ICER = $37, 652/QALY) compared to TAU. At three and five years, net QALYs gained were greater in DBS than TAU by 0.36 and 0.59, respectively. At willingness-to-pay thresholds of $50, 000/QALY for definitive cost-effectiveness and $100, 000/QALY for moderate cost-effectiveness, rechargeable DBS was moderately more cost-effective than TAU at 3 years in 100% and more cost-effective at 5 years in 96% of iterations. CONCLUSIONS: Compared to TAU, in the U.S., rechargeable DBS for TROCD is more cost-effective under a range of possible cost and effectiveness values. However, non-rechargeable DBS is not more cost-effective than TAU for TROCD due to high costs of battery replacement.